MODEL OF THE INFLUENCE OF QUALITY OF WORK LIFE (QWL) ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AT AMAL SEHAT HOSPITAL SRAGEN, CENTRAL JAVA, 2024 - Lailly, Mirna Fauziah; Jayanagara, Oscar (LPPM STIE Muhammadiah Bandung, 2024)
This research aims to explore the effect of Quality of Work Life (QWL) on employee performance, with Organizational Citizenship Behavior (OCB) acting as a mediator, at Amal Sehat Sragen Hospital in Central Java in 2024. Employing a quantitative research approach, data was gathered through a non-probability sampling method, specifically purposive sampling. Surveys were administered to and completed by 77 hospital employees. The collected data was examined using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that Organizational Citizenship Behavior significantly impacts Employee Performance. Additionally, Quality of Work Life positively affects Organizational Citizenship Behavior and directly influences Employee Performance. The study also demonstrates that Quality of Work Life indirectly boosts Employee Performance by positively affecting Organizational Citizenship Behavior. This research provides valuable insights into the mechanisms through which QWL can foster desirable workplace behaviors and ultimately enhance employee performance in healthcare settings like Amal Sehat Sragen Hospital.